Regulation of the cell cycle by the cdk2 protein kinase in cultured human fibroblasts. - Michele Pagano; Rainer Pepperkok; Jiří Lukáš; Véronique Baldin; W. Ansorge; Jiří Bártek; Giulio Draetta (1993)
In mammalian cells inhibition of the cdc2 function results in arrest in the G2-phase of the cell cycle. Several cdc2-related gene products have been identified recently and it has been hypothesized that they control earlier cell cycle events. Here we have studied the relationship between activation of one of these cdc2 homologs, the cdk2 protein kinase, and the progression through the cell cycle in cultured human fibroblasts. We found that cdk2 was activated and specifically localized to the nucleus during S phase and G2. Microinjection of affinity-purified anti-cdk2 antibodies but not of affinity-purified anti-cdc2 antibodies, during G1, inhibited entry into S phase. The specificity of these effects was demonstrated by the fact that a plasmid-driven cdk2 overexpression counteracted the inhibition. These results demonstrate that the cdk2 protein kinase is involved in the activation of DNA synthesis.